A FATAL CASE OF PERSISTENT BURKHOLDERIA PSEUDOMALLEI BACTERAEMIA WITH SEVERE PNEUMONIA AND SPLENIC ABSCESS - Chang, Chee Yik; Lee, Hui Ling (Journal of Ayub Medical College Abbottabad, 2023)
Burkholderia pseudomallei is a Gram-negative bacterium that causes melioidosis. Melioidosis is a potentially fatal disease that is endemic in Southeast Asia and Northern Australia, and is being increasingly recognized in other regions worldwide. Melioidosis can affect any organ system and present with a wide range of clinical manifestations including pneumonia, bone, skin/soft tissue, or central nervous system infections. In this report, we describe a diabetic farmer who succumbed to persistent B. pseudomallei bacteraemia with multiorgan involvement despite treatment with meropenem and ceftazidime.